Advances in osteosynthesis - a basic overview of modern fixation materials - Kozioł, Maciej; Piech, Piotr; Wokurka, Wojciech; Maciejewski, Ryszard (Journal of Education, Health and Sport, 2022)
The dynamic development of trauma-orthopedic surgery and accompanying material technology has led in recent years to the need for close cooperation between researchers in these fields. In a short time, thanks to the cooperation of engineers and doctors, the general approach to the method of bone anastomosis has changed significantly. The need to optimize the effects of treatment, i.e. to quickly recovery, reduce the number of postoperative complications, reduce the number of reoperations, and reduce the costs of procedures and treatment used has resulted in the development of many new technologies that have set trends in modern traumatology. The widespread use of LCP (Locking compression plate) and locking screws, the development of polymers and biopolymers with a modified chemical structure, a significant improvement in the biocompatibility and cytocompatibility of the materials used, and the implementation of products with significant micro-roughness that improve osseointegration are the well-known and commonly used effects of this cooperation today . Materials science related to orthopedics is an extremely complex and multi-threaded field. Its continuous development requires a periodic summary of the results and development directions provided, which allows faster evaluation and interpretation by researchers. The purpose of the following work is to summarize the latest research on materials and methods used in osteosynthesis in a legible way for potential recipients of this information from various fields.